THEORETICAL FOUNDATIONS OF PROJECT-ORIENTED DIGITAL LITERACY TEACHING IN INCLUSIVE EDUCATION - Yersultanova А.С.; Karelkhan Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
Digital technologies in support of inclusive education are one of the effective tools for the development, education and training of persons with special educational needs. The article provides a theoretical analysis of the conditions for teaching digital literacy in inclusive education with a project orientation substantiates effective teaching methods and examines the features of teaching the subject of digital literacy in general education organizations to students with special educational needs. . These methods make digital literacy accessible to all students. Digital inclusion is a form of social inclusion in a digital society aimed at overcoming inequality and digital isolation of citizens. Therefore, the use of all the possibilities of using effective methods of teaching inclusive classes in teaching digital literacy is closely related to the level of teacher training. Considering this, it is important to present the results of the concepts of domestic and foreign studies as additional material.